Measurement of glycine in the human brain in vivo by (1)H-MRS at 3T: Application in brain tumors - Choi, Changho (2011)
Glycine (Gly) is a key metabolic intermediate required for the synthesis of proteins, nucleic acids and other molecules, and its detection in cancer could therefore provide biologically relevant information about the growth of the tumor. Here we report measurement of Gly in human brain and gliomas by an optimized point-resolved spectroscopy (PRESS) sequence at 3T. Echo time dependence of the major obstacle, myo-inositol (mI) multiplet, was investigated with numerical simulations, incorporating the 3D volume localization. The simulations indicated that a subecho pair (TE(1), TE(2)) = (60, 100) ms permits detection of both Gly and mI with optimum selectivity. In vivo validation of the optimized PRESS was conducted on the right parietal cortex of five healthy volunteers. Metabolite signals estimated from LCModel were normalized with respect to the brain water signal and the concentrations were evaluated assuming the total creatine concentration at 8 mM. The Gly concentration was estimated as 0.6±0.1 mM (mean±SD, n=5), with a mean Cramér-Rao lower bound of 9±1%. The PRESS sequence was applied to measure the Gly levels in patients with glioblastoma multiforme. Metabolite concentrations were obtained using the water signal from the tumor mass. The study revealed that a subset of human gliomas contains glycine levels elevated 1.5–8 fold relative to normal.